EFEKTIVITAS PROGRAM INOVASI GABUNGAN AKSI DI SEKOLAH DAN DESA (GADIS DESA) DI KABUPATEN BULUKUMBA - Alistriani, Windi; Abdi, Abdi; Wahid, Nur (Universitas Muhammadiyah Makassar, 2024)
This study aims to determine the effectiveness of the Disdukcapil Village Girls Innovation Program in Bulukumba District. This type of research is descriptive qualitative research, with interview observation methods. Interviews were conducted on 8 informants using purposive sampling. The analysis used is a data validation technique through data triangulation techniques. The results of the research on the 3 approach methods show that the Input approach is in accordance with the expected target and most people already have KTPs, but the facilities and infrastructure are lacking. Then the service process is good enough as seen from the administrative requirements that are clearly socialized to the public, and the output is assessed from human resources that are good enough because they have intellectual qualities both in terms of knowledge, abilities and skills, and have carried out technical guidance. There needs to be socialization to students first before implementing the program at school. In addition, it is necessary to improve facilities and infrastructure in implementing the program so that it can be implemented 100%.